2006
DOI: 10.1038/sj.jhh.1001979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eccentric and concentric resistance training on arterial stiffness

Abstract: It has been suggested that resistance training (RT) increases arterial stiffness. The purpose of the present study was to clarify the effect of eccentric RT (ERT) and concentric RT (CRT) on arterial stiffness in female adults by an interventional study. In total, 29 healthy female subjects were randomly assigned to either the ERT group (n ¼ 10), CRT group (n ¼ 10) or sedentary (SED) group (n ¼ 9). The ERT and CRT groups performed resistance training three times a week for 8 weeks. We determined brachial blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
1
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 42 publications
3
93
1
16
Order By: Relevance
“…24 However, high-intensity resistance training increased arterial stiffness. [10][11][12] On the basis of these results, resistance training may have to be prescribed carefully. The results of this study indicated that CRT increases arterial stiffness, whereas ERT suppresses arterial stiffness increases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 However, high-intensity resistance training increased arterial stiffness. [10][11][12] On the basis of these results, resistance training may have to be prescribed carefully. The results of this study indicated that CRT increases arterial stiffness, whereas ERT suppresses arterial stiffness increases.…”
Section: Discussionmentioning
confidence: 99%
“…However, high-intensity resistance training reduces arterial compliance and increases arterial stiffness. [10][11][12] Muscle contractions during resistance training are performed by eccentric (ECC, lowering phase), concentric (CON, lifting phase) or isometric muscle contractions. Because ECC and CON are contraction modes accompanied by joint movement, they are widely used in typical resistance training.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast with the favorable effects of aerobic exercise, high-intensity resistance training may negatively affect vascular function. 1,2 Arterial blood pressure during high-intensity resistance exercise can increase to 320/250 mm Hg. 3 An extremely high blood pressure increase brings about an decrease of elastin and an increase of collagen, which regulates the elasticity of the artery.…”
mentioning
confidence: 99%